SYSTEMATIC LITERATURE REVIEW (SLR): CHARACTERISTICS OF SELF-AWARENESS IN SHAPING THE CHARACTER OF PROSPECTIVE TEACHERS - Ertanti, Devi Wahyu; Nusantara , Toto; Mashfufah, Aynin; Zuniga, Kristina (Thufuli, 2024)
This research investigates the characteristics of self-awareness that play a crucial role in shaping the character of prospective primary school teachers or Madrasah Ibtidaiyah (MI). The research focused on understanding the level and type of self-awareness of future teachers at the primary education level. Qualitative research methods were used to collect data through in-depth interviews and observations of future primary school teachers. The research findings identified that self-awareness involves a deep understanding of personal values, strengths and weaknesses and their impact on teaching practices. In addition, this study explored how self-awareness can motivate prospective teachers to adapt to classroom situations and build empathetic relationships with students. The results of this study can provide valuable guidance for developing future teacher training programmes at the primary level, taking into account the importance of developing self-awareness in shaping positive and empowered character.